THE RANGE OF SOFT POWER OF THE REPUBLIC OF SERBIA IN THE POST-YUGOSLAV AREA - Todorović, Marina; Lazović, Danica (Political Review, 2024)
The states created after the breakup of Yugoslavia, in modern circumstances, continue to cooperate in various socio-political areas, although their mutual relations are largely shaped by a rich history and burdened by events from the end of the 20th century, which often represent an obstacle in fulfilling the full potential of cooperation and mutual influence. Regardless of the obstacles that objectively exist, it is necessary to take into account the similarities between the people of states that emerged from Yugoslavia, which significantly affect the manifestation of soft power. The research is theoretically based on Joseph Nye’s concept of soft power. In the methodological sense, the research is based on the scientific method of interview. During the research process, methods of content and discourse analysis, historical methods, as well as induction and deduction methods were used. The basic research question that the authors strive to answer is: What is the perception of the soft power of the Republic of Serbia in the post-Yugoslav area? The paper offers the answer to the question What are the basic obstacles and the most prominent potentials of the soft power of the Republic of Serbia in the post-Yugoslav space? The research results indicate that the countries of the post-Yugoslav area are to a high extent susceptible to the soft power influence of Serbia, which is facilitated by the factors of mutual historical, cultural, and linguistic interconnectedness. However, the findings of the research show that in addition to the factors of mutual connection, which facilitate the influence of the soft power of the Republic of Serbia, other factors tend to weaken the possibility of the influence of Serbia’s soft power. The scope of Serbia’s soft power in the post-Yugoslav countries is most visible in the sphere of culture, music, films, TV series, and contemporary literature. In addition, Serbia’s potential is reflected in its capacity to initiate social, political, and cultural regional initiatives, as well as reconciliation initiatives. The results indicate that Serbia is seen as a regional factor that can influence the expansion of soft power in the post-Yugoslav sphere through economic activity. The biggest obstacles to projecting Serbia’s soft power relate to the war legacy from the end of the last century, opposing narratives about controversial historical events, unresolved bilateral disputes, but also prejudices associated with the negative image of Serbia at the time of the breakup of Yugoslavia.